Physiology of Astroglial Excitability. Issue 2 (4th September 2020) - Verkhratsky, Alexei; Semyanov, Alexey; Zorec, Robert
Abstract: Classic physiology divides all neural cells into excitable neurons and nonexcitable neuroglia. Neuroglial cells, chiefly responsible for homeostasis and defense of the nervous tissue, coordinate their complex homeostatic responses with neuronal activity. This coordination reflects a specific form of glial excitability mediated by complex changes in intracellular concentration of ions and second messengers organized in both space and time. Astrocytes are equipped with multiple molecular cascades, which are central for regulating homeostasis of neurotransmitters, ionostasis, synaptic connectivity, and metabolic support of the central nervous system. Astrocytes are further provisioned with multiple receptors for neurotransmitters and neurohormones, which upon activation trigger intracellular signals mediated by Ca 2+, Na +, and cyclic AMP. Calcium signals have distinct organization and underlying mechanisms in different astrocytic compartments thus allowing complex spatiotemporal signaling. Signals mediated by fluctuations in cytosolic Na + are instrumental for coordination of Na + dependent astrocytic transporters with tissue state and homeostatic demands. Astroglial ionic excitability may also involve K +, H +, and Cl − . The cyclic AMP signalling system is, in comparison to ions, much slower in targeting astroglial effector mechanisms. This evidence review summarizes the concept of astroglial intracellular excitability.